ANALISIS IMPLEMENTASI MICROTEACHING DALAM PENGEMBANGAN KETERAMPILAN DASAR MENGAJAR CALON GURU IPS - Soraya, Siti Zazak; Harisatunisa, Harisatunisa; Musyahid, Musyahid (LPPM IKIP PGRI Pontianak, 2023)
The objective of this study was to examine how microteaching is implemented to enhance the fundamental teaching skills of future Social Studies teachers. This research employed a quantitative descriptive approach, utilizing observation rubrics and performance assessment as data collection methods. The study's sample was 18 students enrolled in the Social Studies Teaching program. The results revealed increased scores on essential teaching skills during the second performance. The detailed evaluation covers questioning skills at 72.5, reinforcement skills at 71.7, variation skills at 73.1, explanation skills at 75.4, opening and closing lesson skills at 75.4, discussion and small group skills at 69.5, class management and discipline skills at 73, individual teaching skills at 75.7, and lesson plan preparation skills at 78.8. In summary, prospective Social Studies teachers have effectively developed their teaching skills. However, further guidance is essential, particularly in discussion and small group management.